Healthcare-associated infections in a newly opened pediatric intensive care unit in Turkey: Results of four-year surveillance - KEPENEKLİ KADAYİFCİ, EDA; ALTINKANAT GELMEZ, GÜLŞEN; ÖZTÜRK, MAKBULE NİLÜFER; YAKUT, NURHAYAT (J INFECTION DEVELOPING COUNTRIES, 2016)
Introduction: Healthcare-associated infections (HAIs) are important causes of morbidity and mortality, especially in critically ill patients in intensive care units. The aim of this study was to assess the rate and distribution of HAIs, pathogens, and antimicrobial susceptibility patterns in a newly opened pediatric intensive care unit (PICU). Methodology: The infection control team detected and recorded HAI cases according to the Centers for Disease Control and Prevention's criteria in the PICU of Marmara University Pendik Training and Research Hospital over a four-year period following its opening. Laboratory-based HAIs surveillance was performed prospectively from 1 January 2011 to 30 November 2014. Results: During the study period, 1,007 patients hospitalized in the PICU and 224 HAIs were identified. The overall HAI rate was 22.24%, and the incidence density was 20.71 per 1,000 patient-days. The most commonly observed HAIs were bloodstream infection (35.7%), pneumonia (21.4%), and urinary tract infection (20.5%), and the three most common HAI pathogens were Klebsiella spp. (19.4%), Pseudomonas aeruginosa (13.8%), and Acinetobacter baumanii (12%). Methicillin resistance was detected in 78% of coagulase-negative Staphylococcus. Presence of extended-spectrum beta-lactamases was determined in 45% and 54% of Klebsiella spp. strains and Escherichia coli isolates, respectively. Conclusions: Our rate of HAIs is higher than the mean rates reported in PICU studies from developed countries. Active surveillance studies of HAIs is an essential component of infection control, which may contribute to improving preventive strategies in developing countries.
Keywords: antibiotic susceptibility patterns; healthcare-associated infections; newly opened pediatric intensive care unit; POINT-PREVALENCE SURVEY; NOSOCOMIAL INFECTIONS; HOSPITALS; STATES